MUHAMMAD ABED AL-JABIRI, NALAR BUDAYA ARAB, DAN IMPLIKASINYA DALAM PENDIDIKAN ISLAM - Ahmad Lahmi; Sandra Ayu (Program Pascasarjana UMSB, 2019)
Abstract: This study was conducted on the thought of Muhammad Abed al-Jabiri, in his work